PreAlgebra
posted by Anonymous on .
Please help!
(a^2)63
(2x)^3
(p^2q)^3
5c(2cd)^3
4y(y62z)63
(12a^5)^2b^3
6a(ab)^7
(2d^2)^6(3)^3
please and thanc u!

Learn and apply these rules for taking powers of numbers with exponents,
(x^a)^b = x^(ab) ,
(x^a*y^b)^c = x^(ac) * y^(bc)
and multiplying variables with exponents.
x^a*x^b = x^(a+b)
Here is how this works with two examples. You should do the rest yourself.
(p^2*q)^3 = p^6*q^3
6a(ab)^7 = 6a*(1)^7 * a^7 * b^7
= 6a^8 * b^7
The * symbol indicates multiplication, but could be left out